Augmented Reality in Child Education: A Bibliometric and Trend Analysis of Global Research (2015–2025) - Yelva Nofriyanti; Andika Bayu Putra; Desmawati Roza; Evi Desmariani; Meria Ultra Gusteti (Postgraduate, University of Mataram, 2026)
This study aims to bibliometrically analyze publication trends, collaboration patterns, and research development directions regarding Augmented Reality (AR) in children's education. Data was obtained from the Scopus database on July 16, 2025 with the keywords